Transformational leadership and work achievement LLDIKTI lecturer, Region IX: The role of empowerment intervening - Jusriadi, Edi; Rusydi, Muhammad; Rahim, Abdul Rahman (Technium Social Sciences Journal, 2022)
This study aimed to examine the effect of transformational leadership on empowerment, the effect of transformational leadership on work performance either directly or through empowerment and examine the effect of empowerment on work performance. This research was explanatory research with a quantitative approach to explain the relationship (causality) between one variable and other variables. The data collection technique used a questionnaire about transformational leadership, work performance, and empowerment to 196 LLDIKTI lecturers in Region IX Sulawesi Island. The data analysis used descriptive and inferential analysis with Structural Equation Model (SEM). The findings of this study reveal that (1) there was a positive and significant effect of transformational leadership on empowerment, but transformational leadership was not significant on work performance, (2) empowerment was found to have a positive and significant effect on work performance. (3) transformational leadership through empowerment can improve work performance. Moreover, empowerment is one of the most important and influential processes within the framework of the transformational leadership model in encouraging work performance among lecturers. Thus, this study extended empirical research on transformational leadership and its effect on job performance through empowerment. Besides, the limitation of this research was using the unit of analysis, which only comes from LLDIKTI lecturers in Region IX Sulawesi, all private universities without involving state universities. This study showed the urgency of efforts to create greater empowerment for LLDIKTI Region IX lecturers and leaders who can significantly contribute to work performance.